2010
DOI: 10.1177/1470320310361742
|View full text |Cite
|
Sign up to set email alerts
|

Renin-angiotensin-aldosterone system gene polymorphisms in coronary artery bypass graft surgery patients

Abstract: There is no association of the analysed RAAS polymorphisms with severe CAD in CABG patients. However, within these patients, an association was found between AGT 235TT genotype and hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 46 publications
2
7
0
1
Order By: Relevance
“…Similar data were obtained by Renner et al, who reported no association of two AGT polymorphisms (rs699 and rs4762) with blood pressure and CAD in German population (Renner et al, 2005). On the other hand, two AGT polymorphisms studied by Ragia et al, were not associated with CAD and coronary artery bypass grafting in Greek population (Ragia et al, 2010). In contrast to these results, Al-Najai et al, reported that the rs5051, and rs699 polymorphisms were associated with risk of developing myocardial infarction in native Saudi population (Al-Najai et al, 2013).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Similar data were obtained by Renner et al, who reported no association of two AGT polymorphisms (rs699 and rs4762) with blood pressure and CAD in German population (Renner et al, 2005). On the other hand, two AGT polymorphisms studied by Ragia et al, were not associated with CAD and coronary artery bypass grafting in Greek population (Ragia et al, 2010). In contrast to these results, Al-Najai et al, reported that the rs5051, and rs699 polymorphisms were associated with risk of developing myocardial infarction in native Saudi population (Al-Najai et al, 2013).…”
Section: Discussionsupporting
confidence: 84%
“…Polymorphisms in the genes that encode these molecules have been associated with risk of developing inflammatory diseases, such hypertension, atherosclerosis, vascular disease, coronary artery disease, blood pressure, coronary artery bypass graft, preeclampsia, and acute pancreatitis (Mansego et al, 2008;Ragia et al, 2010;Dzielinska et al, 2011;Abd El-Aziz et al, 2012;Al-Najai et al, 2013;Brugts et al, 2011;Wang et al, 2014;Skipworth et al, 2015;Mirsha et al, 2012). In the present work, we studied seven polymorphisms, five located in the AGT gene and two located in the REN gene.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…By virtue of the function of AGT in regulating blood pressure, changes in its gene sequence are likely to play an important role in the pathogenesis of cardiovascular risk traits, such as hypertension, as well as manifestation of coronary artery disease (CAD) [2,3]. Several AGT variants, including the rs4762 (p.M207T, also formerly known as p.T174M) and rs699 (p.M268T, also referred to as p.M235T), have been associated with susceptibility to various cardiovascular risk traits, such as primary hypertension (HTN) [4-10] and type 2 diabetes (T2DM) [11,12], that are linked to the development of CAD. These variants have similarly been implicated not only in the manifestation of CAD [13-23], but also in the severity of atherosclerosis [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…(Procopciuc et al, 2002). et al, 2003) 109/86 M F Turkia HE TT (Araujo et al, 2005) 201/104 M F Brasil DAC e IM NS (Fardella et al, 1998) 64/62 M F Chile PS TT (Fatini et al, 2000) 205/209 M F Itália DAC NS (Glavnik ePetrovic, 2007) 413/404 M F Eslovênia HE NS a (Lanz et al, 2005) 871 M F Brasil DAC b TT e T (Mondorf et al, 1998) 121/125 M F Alemanha HE NS (Mondry et al, 2005) 638/720 M F Alemanha HE TT c (Procopciuc et al, 2002) 38/21 M F Romênia HE TT e T (Ragia et al, 2010) 154/155 M F Grécia DAC NS (Ragia et al, 2010) 154/155 M F Grécia HE TT (Rodriguez-Perez et al, 2001) 304/315 M F Espanha DAC TT (Say et al, 2005) posição 235 (M235T) e foi significantemente associado com o risco de hipertensão (Niu et al, 1999)…”
Section: Aspectos Genéticos Da Hipertensãounclassified